2005
DOI: 10.1242/jcs.02276
|View full text |Cite
|
Sign up to set email alerts
|

Classical protein kinase C(s) regulates targeting of synaptotagmin IX to the endocytic recycling compartment

Abstract: Neuronal and non-neuronal tissues show distinctly different intracellular localization of synaptotagmin (Syt) homologues. Therefore, cell type-specific mechanisms are likely to direct Syt homologues to their final cellular destinations. Syt IX localizes to dense core vesicles in PC12 cells. However, in the rat basophilic leukemia (RBL-2H3) mast cell line, as well as in CHO cells, Syt IX is localized at the endocytic recycling compartment (ERC). We show that targeting of Syt IX to the ERC involves constitutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…2C). These two forms of Syt V may represent different posttranslational modifications, such as phosphorylation, as previously observed with Syt IV and Syt IX (36,37). We next compared the recruitment kinetics of Syt V and LAMP1 to phagosomes containing serum opsonizedzymozan by confocal microscopy.…”
Section: Syt V Associates To Phagosomesmentioning
confidence: 82%
“…2C). These two forms of Syt V may represent different posttranslational modifications, such as phosphorylation, as previously observed with Syt IV and Syt IX (36,37). We next compared the recruitment kinetics of Syt V and LAMP1 to phagosomes containing serum opsonizedzymozan by confocal microscopy.…”
Section: Syt V Associates To Phagosomesmentioning
confidence: 82%
“…Many studies have implicated PKC in the internalization of specific receptors, transporters, and channels (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Some of these studies have focused on direct phosphorylation of these molecules by PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are several examples in the literature showing PKC-dependent sequestration of molecules such as the dopamine transporter (14,15), dopamine receptor (42), parathyroid hormone receptor (43), norepinephrine transporter (16), human cationic amino acid transporter (17), and synaptotagmin IX (18)) to a compartment that resembles the pericentrion. Although those studies focused on specific PKC/target interaction, our results would suggest that the effects of PKC in those cases as well may be part of the more generalized effects on recycling endosomes described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rotmann et al (17) found that treatment of cells with PMA resulted in internalization (possibly to the pericentrion) of the human cationic amino acid transporter hCAT-1. Furthermore, synaptotagmin IX was shown to be internalized to a compartment that resembles the pericentrion in a PKC␣-dependent manner (18). All these data indicate that active PKC␣ can indeed selectively regulate sequestration of certain molecules from the cell surface.…”
Section: Members Of the Protein Kinase C (Pkc)mentioning
confidence: 91%